2020
DOI: 10.3390/cryst10040275
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Inhibition of Calcium Carbonate Crystals under Cathodic Polarization Conditions

Abstract: The formation of CaCO3 crystals on the cathode surface and the scale-inhibition performance of scale inhibitor 2-phosphonobutane-1,2,4-tricarboxylic acid (PBTCA) on the cathode surface were studied by methods of solution analysis, gravimetric analysis, SEM, FTIR, and XRD techniques. They were then compared with the results of the formation and suppression of CaCO3 crystals in aqueous solution. PBTCA had a good solution-scale-inhibition performance and good lattice-distortion effects on CaCO3 crystals in soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…However, EDTA and citric acid with insufficient antiscaling efficacy exhibited the most gypsum crystals habit modification, while ATMP with the highest efficacy revealed no noticeable changes in crystal morphology. Recently, a similar conclusion concerning CaCO 3 deposition in the presence of PBTC was reported: the scale inhibition effect of PBTC under cathodic polarization has no obvious relationship on the crystal habit modification, caused by PBTC [32].…”
Section: Visualization Of Paa-f2 In a Binary Gypsum-paa-f2 Systemsupporting
confidence: 53%
“…However, EDTA and citric acid with insufficient antiscaling efficacy exhibited the most gypsum crystals habit modification, while ATMP with the highest efficacy revealed no noticeable changes in crystal morphology. Recently, a similar conclusion concerning CaCO 3 deposition in the presence of PBTC was reported: the scale inhibition effect of PBTC under cathodic polarization has no obvious relationship on the crystal habit modification, caused by PBTC [32].…”
Section: Visualization Of Paa-f2 In a Binary Gypsum-paa-f2 Systemsupporting
confidence: 53%
“…At the same time, unlike HEDP-F, polyacrylate definitely causes a well-expressed crystal morphology change of calcium carbonate (Figure 10d). Although such effects have been registered earlier both in our experiments [28], and in experiments of other research groups [29,30], this observation should still be noted. The less efficient antiscalant PAA-F1 causes morphology change of calcite, while the more efficient HEDP-F does not.…”
Section: Sem and Fm Analysis Of Membrane Surfacesupporting
confidence: 59%
“…However, there is a lack of direct correlation between inhibition efficacy and crystal distortion. Some other authors have revealed that the least efficient scale inhibitors, instead of the most efficient inhibitors, have a higher tendency to change the morphology of scale crystals [71,72]. More investigations should be conducted to clarify the crystal modification mechanism.…”
Section: Crystal Modificationmentioning
confidence: 96%